Challenges and Opportunities in the Continuity of Care for Hypertension : A Mixed-Methods Study Embedded in a Primary Health Care Intervention in Tajikistan - Chukwuma, Adanna (Springer Nature, 2021)
Hypertension, a significant risk factor for ischemic heart disease and other chronic conditions, is the third-highest cause of death and disability in Tajikistan. Thus, ensuring the early detection and appropriate management of hypertension is a core element of strategies to improve population health in Tajikistan. For a strategy to be successful, it should be informed by the causes of gaps in service delivery and feasible solutions to these challenges. The objective of this study was to undertake a systematic assessment of hypertension case detection and retention in care within Tajikistan’s primary health care system, and to identify challenges and appropriate solutions. We review the results for the case detection stage of the cascade of care, which had the most significant gaps. Of the half a million people with hypertension in Khatlon and Sogd Oblasts (administrative regions), about 10% have been diagnosed in Khatlon and only 5% in Sogd. Barriers to case detection include misinformation about hypertension, ambiguous protocols, and limited delivery capacity. Solutions identified to these challenges were mobilizing faith-based organizations, scaling up screening through health caravans, task-shifting to increase provider supply, and introducing job aids for providers. Translating findings on discontinuities in care for hypertension and other chronic diseases to actionable policy insights can be facilitated by collaboration with local stakeholders, triangulation of data sources, and identifying the intersection between the feasible and the effective in defining solutions to service delivery challenges.